Women as Icons in the Economic Development of Kuron Pottery Making in Sabah - Nurul Aisyah Othman; Humin Jusilin; Salbiah Kindoyop (2018)
There is no doubt in this age the role of women in economic development is no longer doubted at present and in fact able to match the capabilities of men. The involvement of women in the effort to provide their contributions and services to the country is not a small sacrifice. There are many things that they need to manage and at the same time balance their career as well as their family lives. This can be seen through the economic development they have achieved particularly in producing the kuron, a Sabah traditional pottery. This type of traditional pottery is usually made by women who are creative in conveying their ideas from a technical point of view, design and unique motifs. The purpose of this research is to highlight the skills and abilities of women as icons in the production of traditional pottery crafts. The researchers look at the women icon in detail using the feminist idea introduced by June Hannam (2007) that emphasizes on the current competitiveness and position of women in improving economic development. The aesthetic elements found in the production of this traditional pottery can not only explain its cultural value but also showcases the functional utility and the important role it plays in developing the economy of kuron pottery in Sabah. This can become a source of income and contribute in generating the country’s economy.